Bricks - Van Der Giet, Julia (Satura, 2022)
Peter has been happily married for years. It hasn’t always been perfect, but he is content. Nowadays he couldn’t imagine a life without his wife. Nicole. She is a part of him. Just like his job, his house, his club are parts of him. All these things make him the man he is. Peter Brick. A fulfilled man with both feet firmly on the ground.